2005
DOI: 10.1049/el:20051160
|View full text |Cite
|
Sign up to set email alerts
|

Static and dynamic properties of laterally coupled DFB lasers based on InAs∕InP QDash structures

Abstract: Laterally coupled, complex distributed feedback lasers based on AlInGaAs=InAs=InP quantum dash layers were fabricated by maskless focused ion beam lithography. Continuous-wave powers above 30 mW at room temperature, sidemode suppression ratios of 44 dB and a modulation bandwidth of 7.6 GHz were demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 9 publications
(12 reference statements)
0
8
0
Order By: Relevance
“…From the temperature dependent measurements, a small shift in the lasing wavelength of 0.1 nm/K (20 to 70ºC) was obtained and has been attributed to the temperature dependence of the active region refractive index. This work was soon followed by Kaiser et al [267] who reported the dynamic properties of laterally coupled DFB gratings based 4 stack InAs/InGaAlAs Qdash laser, as shown in Fig. 39(a).…”
Section: Single Mode Lasersmentioning
confidence: 98%
“…From the temperature dependent measurements, a small shift in the lasing wavelength of 0.1 nm/K (20 to 70ºC) was obtained and has been attributed to the temperature dependence of the active region refractive index. This work was soon followed by Kaiser et al [267] who reported the dynamic properties of laterally coupled DFB gratings based 4 stack InAs/InGaAlAs Qdash laser, as shown in Fig. 39(a).…”
Section: Single Mode Lasersmentioning
confidence: 98%
“…For comparison, we note that a temperature coefficient of 0.092 nm/K has been measured in 1.55 lm GaInAsP/InP LC-DBR lasers, 49 while values of 0.11 nm/K and 0.14 nm/K have been extracted for AlGaInAs/InAs/InP Qdash based LC-DFB lasers emitting at 1.55 lm (Ref. 50) and 2 lm (Ref. 9), respectively, and 0.11 nm/K for InGaAs/lnGaAsP QW based DFB lasers at 1.95 lm.…”
Section: Resultsmentioning
confidence: 99%
“…Distributed feedback lasers with laterally defined gratings reach modulation bandwidths beyond 7.5 GHz [13], which will make 10 GBit/s data transmission possible. Nevertheless, the bandwidth of quantum dots lasers in general is more limited in bandwidth than previously expected.…”
Section: Inp Based Quantum Dashes Lasersmentioning
confidence: 99%